UJI EFEKTIFITAS EKSTRAK DAUN SRIKAYA (Anonna squamosa) TERHADAP KEMATIAN KECOA AMERIKA (Periplaneta americana) - Wahyuni, Denai; Anggraini, Reni (Sistem Informasi, 2018)
Cockroaches as mechanical vectors for some pathogenic microorganisms such as: Streptococus, Salmonella and contributing to spread diseases of dysentery, diarrhea, cholera, hepatitis A viruses and Polio. Controling of cockroaches presents using synthetic insecticides but it can be subtitutes by naturalinsecticides that called srikaya leaf extract. The aims of this study to looked the content of secondary metabolite compounds in srikaya leaves, determining the mortality of cockroaches and LC50. This study used 6 cockroaches with concentrations of 5%, 10%, 20% and 30%, K (+) baygon, K (-) aquades with 3 times replications and observed for 3 hours. The data were analyzed using Probit Analysis to determine LC50. The result of identification of phytochemical compound, srikaya leaf contains flavonoid, saponin, alkaloid and tannin. The percentage mortality of cockroach at concentration 5%, 10%, 20%, and 30% respectively were 11,11%, 22,22%, 27,77%, and 53,33% with LC50 346.736 ppm.